2009
DOI: 10.1038/emboj.2009.255
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial ‘kiss-and-run’: interplay between mitochondrial motility and fusion–fission dynamics

Abstract: Visualizing mitochondrial fusion in real time, we identified two classes of fusion events in mammalian cells. In addition to complete fusion, we observed transient fusion events, wherein two mitochondria came into close apposition, exchanged soluble inter-membrane space and matrix proteins, and re-separated, preserving the original morphology. Transient fusion exhibited rapid kinetics of the sequential and separable mergers of the outer and inner membranes, but allowed only partial exchange of integral membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
286
2
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(316 citation statements)
references
References 66 publications
20
286
2
1
Order By: Relevance
“…In turn, lower motility decreases the number of contacts and the fusion rate. The latter conclusion is consistent with previous findings that inhibition of mitochondrial movement by nocodazol and vasopressin in H9c2 cells also inhibited mitochondrial fusion (Liu et al, 2009). Similarly, a recent study by Twig et al suggested that mitochondrial motility facilitates mitochondrial fusion in H9c2 and INS1 cells (Twig et al, 2010).…”
Section: Self-regulation Of Mitochondrial Lengthsupporting
confidence: 92%
“…In turn, lower motility decreases the number of contacts and the fusion rate. The latter conclusion is consistent with previous findings that inhibition of mitochondrial movement by nocodazol and vasopressin in H9c2 cells also inhibited mitochondrial fusion (Liu et al, 2009). Similarly, a recent study by Twig et al suggested that mitochondrial motility facilitates mitochondrial fusion in H9c2 and INS1 cells (Twig et al, 2010).…”
Section: Self-regulation Of Mitochondrial Lengthsupporting
confidence: 92%
“…This "kissand-run" mechanism would provide an efficient means for delivering iron to mitochondria in RBCs, which generate vast amounts of heme. Recent evidence showed that mitochondria fuse with each other and with the endoplasmic reticulum (21,22). Small organic compounds or some proteins may also bind free cellular iron (23).…”
Section: Mitochondrial Iron Uptake and Processingmentioning
confidence: 99%
“…Fission allows distribution of mitochondria to daughter cells following mitosis. Small mitochondria are more efficiently tracked along the cytoskeleton , which also allows a quality control mechanism to exist where fragmented 'old' mitochondria can be turned over by autophagy [2]. Fusion enables mitochondrial contents to be mixed between neighbouring organelles.…”
Section: Hot Off the Pressmentioning
confidence: 99%